Comorbidity in Multiple Sclerosis - Magyari, Melinda; Sorensen, Per Soelberg (Frontiers in neurology, 2020)
Comorbidities in patients with multiple sclerosis (MS) has become an area of increasing interest in the recent years. A comorbidity is defined as any additional disease that coexists in an individual with a given index disease and that is not an obvious complication of the index disease. The aim of this review is to describe the current evidence regarding the range of comorbidities in the population with MS reported in different countries and the current knowledge about the influence of comorbidities on the clinical features and therapeutic challenges in MS. Certain comorbidities are more prevalent in people with MS such as depression, anxiety, cerebro- and cardiovascular diseases, and certain autoimmune disorders such as diabetes, thyroid disease, and inflammatory bowel disease. A previous perception of a trend toward a lower overall risk of cancer in patients with MS appears to be challenged, but there is no evidence on any higher occurrence of malignancies in the population with MS. Comorbidities may modify the clinical presentation of MS, and have implications for treatment choice, adherence, and outcome. Several comorbid conditions are associated with increased disability progression, including diabetes, hypertension, and chronic obstructive pulmonary disease. Comorbidities are common in MS from the time of diagnosis and may account for some of the heterogeneity observed in MS, including diagnostic delay, clinical presentation, degree of disability progression, rate of health care utilization, working ability, employment status, and quality of life. Coexisting diseases and polypharmacy increase the complexity of patient management and poses major challenges, particularly with the increasing number of immunosuppressive disease-modifying therapies.Comorbidities in patients with multiple sclerosis (MS) has become an area of increasing interest in the recent years. A comorbidity is defined as any additional disease that coexists in an individual with a given index disease and that is not an obvious complication of the index disease. The aim of this review is to describe the current evidence regarding the range of comorbidities in the population with MS reported in different countries and the current knowledge about the influence of comorbidities on the clinical features and therapeutic challenges in MS. Certain comorbidities are more prevalent in people with MS such as depression, anxiety, cerebro- and cardiovascular diseases, and certain autoimmune disorders such as diabetes, thyroid disease, and inflammatory bowel disease. A previous perception of a trend toward a lower overall risk of cancer in patients with MS appears to be challenged, but there is no evidence on any higher occurrence of malignancies in the population with MS. Comorbidities may modify the clinical presentation of MS, and have implications for treatment choice, adherence, and outcome. Several comorbid conditions are associated with increased disability progression, including diabetes, hypertension, and chronic obstructive pulmonary disease. Comorbidities are common in MS from the time of diagnosis and may account for some of the heterogeneity observed in MS, including diagnostic delay, clinical presentation, degree of disability progression, rate of health care utilization, working ability, employment status, and quality of life. Coexisting diseases and polypharmacy increase the complexity of patient management and poses major challenges, particularly with the increasing number of immunosuppressive disease-modifying therapies.